HAK TENAGA KESEHATAN MENOLAK PELAYANAN KESEHATAN YANG TIDAK SESUAI STANDARD IGD RUMAH SAKIT DI SEMARANG - Cuk Samsul Arif; Markus Suryo Utomo (Badan Penerbit STIEPARI Press, 2022)
The purpose of this study was to examine and analyze the rights of health workers who refuse health services that do not meet the standards of the Emergency Room Hospital in Semarang and what factors influence the implementation of these health worker rights. The research approach uses normative juridical, research data uses secondary data, and uses secondary legal materials, namely articles, research papers and books. The results of the study (1) The right of health workers to refuse health services that do not comply with hospital emergency room standards will result in an illegal act. If the hospital is proven to have committed an unlawful act and fulfills the elements of an unlawful act, the hospital can be held accountable and can be subject to sanctions in accordance with the applicable laws and regulations. (2). The influencing factors are the hospital's commitment to maintaining health services according to hospital accreditation standards, good communication, available information facilities, insights of health workers about health laws, and people's lack of understanding of laws.